TARPTAUTINĖ BENDRUOMENĖ PRIVALO RŪPINTIS KIEKVIENO ASMENS BIOETIKOS APSAUGA – SUFORMUOTI BENDRĄ TARPTAUTINIŲ IR NACIONALINIŲ BIOETIKOS TEISMŲ SISTEMĄ - Tretiakova, Victoria Grygoryevna Grygoryevna (Teisė, 2013)
The author made a research on the state of development human rights bioethical legislation and judicial protection of bioethical rights under intensive development of civil society, in which everybody’s life, health, physical and mental integrity and dignity are core value for the latter, and thus require immediate attention of every democratic state. The author makes her proposals for unified specialized bioethical justice and unified system of specialized bioethical courts at the international, regional and national levels, justifying necessity of them by specific nature of bioethical legal relations and socially based prioritisation of the protection of bioethical rights.